Poly(I:C) increases the expression of mPGES-1 and COX-2 in rat primary microglia. Issue 1 (December 2016) - de Oliveira, Antonio; Yousif, Nizar; Bhatia, Harsharan; Hermanek, Julia; Huell, Michael; Fiebich, Bernd
Abstract Background Microglia recognize pathogen-associated molecular patterns such as double-stranded RNA (dsRNA) present in some viruses. Polyinosinic-polycytidylic acid [poly(I:C)] is a synthetic analog of dsRNA that activates different molecules, such as retinoic acid-inducible gene I, melanoma differentiation-associated gene 5, and toll-like receptor-3 (TLR3). Poly(I:C) increases the expression of different cytokines in various cell types. However, its role in the regulation of the production of inflammatory mediators of the arachidonic acid pathway by microglia is poorly understood. Methods In the present study, we evaluated the effect of poly(I:C) on the production of prostaglandin E2 (PGE2 ) and the inducible enzymes cyclooxygenase-2 (COX-2) and microsomal prostaglandin E synthase-1 (mPGES-1) in primary rat microglia. Microglia were stimulated with different concentrations of poly(I:C) (0.1–10 μg/ml), and the protein levels of COX-2 and mPGES-1, as well as the release of PGE2, were determined by western blot and enzyme immunoassay (EIA), respectively. Values were compared using one-way ANOVA with post hoc Student-Newman-Keuls test. Results Poly(I:C) increased the production of PGE2, as well as mPGES-1 and COX-2 synthesis. To investigate the mechanisms involved in poly(I:C)-induced COX-2 and mPGES-1, we studied the effects of various signal transduction pathway inhibitors. Protein levels of COX-2 and mPGES-1 were reduced by SB203580, SP600125, and SC514 (p38 mitogen-activated protein kinase (MAPK), c-Jun N-terminal kinase (JNK), and IκB kinase (IKK) inhibitors, respectively), as well as by PD98059 and PD0325901 (mitogen-activated protein kinase kinase (MEK) inhibitors). Rapamycin, a mammalian target of rapamycin (mTOR) inhibitor, enhanced the synthesis of COX-2. Inhibition of phosphatidylinositol 3-kinase (PI3K) by LY294002 or dual inhibition of PI3K/mTOR (with NVP-BEZ235) enhanced COX-2 and reduced mPGES-1 immunoreactivity. To confirm the data obtained with the inhibitors, we studied the phosphorylation of the blocked kinases by western blot. Poly(I:C) increased the phosphorylation of p38 MAPK, extracellular signal-regulated kinase (ERK), JNK, protein kinase B (Akt), and IκB. Conclusions Taken together, our data demonstrate that poly(I:C) increases the synthesis of enzymes involved in PGE2 synthesis via activation of different signaling pathways in microglia. Importantly, poly(I:C) activates similar pathways also involved in TLR4 signaling that are important for COX-2 and mPGES-1 synthesis. Thus, these two enzymes and their products might contribute to the neuropathological effects induced in response to dsRNA, whereby the engagement of TLR3 might be involved.